THE EFFECT OF TEMPERATURE VARIATION ON RESISTANCE VALUE IN ELECTRICITY CIRCUITS - Ridwan Yusuf Lubis; Lailatul Husna Lubis; Miftahul Husnah (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2020)
Temperature is the level of heat in an object and one of the variables that gives an influence on the value of an object's electrical resistance. The value of electrical resistance affects the conductivity of objects. This study aims to determine the change in the value of resistance in the wire connected to the heater. The benefit of this research is to provide information to the public about the effect of temperature changes on the value of electrical resistance. This study uses an experimental method by measuring the resistance values on wire 1 and wire 2 which are at room temperature and influenced by heat sources. Changes in temperature towards higher values make free electrons in the wire move faster. The higher the temperature value, the higher the value of resistance produced by the wire.